Shaping Scholarly Recognition in Early Nineteenth-Century Poland: The Case of the Society of the Friends of Sciences (1800–1832) - Adrian Wesołowski (Zeitschrift für Ostmitteleuropa-Forschung)
This article addresses the challenges faced by nineteenth-century scholars and scientists, particularly in partitioned Poland, as they navigated the loss of traditional political representation. In a context where political authority was eroded, intellectuals sought new ways to assert their visibility and influence within the public sphere. Focusing on the Warsaw Society of the Friends of Sciences, the study examines how its members positioned themselves as alternative representatives of the Polish public through strategic self-presentation and developing a new discourse on scholarly fame. By promoting a new image of the scholar as both intellectually engaged and socially active, the Society aimed to elevate its public profile and offer Poles a new form of cultural representation amidst political disenfranchisement.